Treatment and biodegradation kinetics of microbially treated domestic wastewater sludge - Alam, Md. Zahangir; Fakhru’l-Razi, A.; Mollah, Abul H. (Marcel Dekker, Inc., 2004)
A laboratory-scale study was undertaken to evaluate the liquid state bioconversion (LSB) in terms of biodegradation of microbially treated domestic wastewater sludge (biosolids) as well as its kinetics. The potential fungal strains and process factors developed from previous studies were used throughout the study. The results presented in this study showed that an effective biodegradation occurred with the biosolids (sludge cake) accumulated. The maximum biosolids (sludge cake) accumulated (93.8 g/kg of liquid sludge) enriched with the biomass protein (30.2 g/kg of dry biosolids), was achieved which improved the effluent quality by enhancing the removal of chemical oxygen demand (COD), reducing sugar (RS),soluble protein (SP), total dissolved solids (TDS), and total suspended solids (TSS). The higher reduction of specific resistance to filtration (SRF) was observed during bioconversion process. The kinetics results showed that the experimental data were better fitted for the biodegradation efficiency, and biosolids accumulation and biodegradation rate.